Benefits and Barriers on Quizizz Application as Formative Assessment Tool in Vocabulary Teaching: Students Side - Sandi, Sandi; Dangin, Dangin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
As technology becomes more advanced, education is getting more sophisticated. The purpose of this study is to find out the benefits and barriers related on Quizizz Application as formative assessment tool in vocabulary teaching for students. This study is classified as qualitative research, the sample of this research is 10 students of SMA N 4 Yogyakarta. Data were collected through observation, interviews and documentation. The study revealed two main aspects, the benefits and the barriers. Analysis of research data is descriptive. The results of the study showed students' perspectives on the use of Quizizz. In conclusion, students' opinions on the usage of Quizizz as formative assessment tool in learning vocabulary are positive, the platform is extremely entertaining to use in the classroom and helps students focus more on the material that they have learned. Keywords: Assessment Tool, Quizizz Application, Vocabulary